2023
DOI: 10.5056/jnm21250
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients With Ineffective Esophageal Motility by Chicago Classification Version 4.0 Compared to Chicago Classification Version 3.0

Abstract: Background/AimsChicago classification version 4.0 (CCv4.0) of esophageal motility disorders developed a more stringent diagnostic criteria for ineffective esophageal motility (IEM) than version 3.0. We studied the implications of the new diagnostic criteria on the prevalence of IEM, and clinically characterized and compared the population of patients who no longer meet diagnostic criteria for IEM to those who retain the diagnosis. MethodsWe included all consecutively performed high-resolution esophageal impeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…42 Chicago classification version 4 (Table 1) was used for the analysis and interpretation of the esophageal manometric data and motility disorders. 43 Readings from both the resting and the 10 wet swallows were analyzed. The main metrics in EHRIM were the integrated relaxation pressure (IRP) of the lower esophageal sphincter (LES), which reflects deglutitive relaxation across the LES, and the distal contractile integral (DCI), which is a pressure integral representing the strength of esophageal contraction.…”
Section: Esophageal High-resolution Impedance Manometrymentioning
confidence: 99%
“…42 Chicago classification version 4 (Table 1) was used for the analysis and interpretation of the esophageal manometric data and motility disorders. 43 Readings from both the resting and the 10 wet swallows were analyzed. The main metrics in EHRIM were the integrated relaxation pressure (IRP) of the lower esophageal sphincter (LES), which reflects deglutitive relaxation across the LES, and the distal contractile integral (DCI), which is a pressure integral representing the strength of esophageal contraction.…”
Section: Esophageal High-resolution Impedance Manometrymentioning
confidence: 99%
“…Supporting tests like impedance or barium esophagram may be required. The new criteria identified IEM more likely associated with GERD [8,9 ▪ ,10].…”
Section: Key Changes In Chicago Classification Version 40mentioning
confidence: 99%
“…Some researchers have shown that patients with short-latency spasm do not differ significantly from those with normal latency spasm in terms of dysphagia symptoms [21]. (6) The CC renders no opinion on whether or how to interpret some commonly observed findings like absent LES tone, retrograde esophageal contractions, and secondary contractions. (7) Because the CC has yet to incorporate concurrent impedance data into the classification system it remains uninformative as to criteria for diagnosing conditions such as rumination, aerophagia, and supragastric belching.…”
Section: Treatment Directionmentioning
confidence: 99%
“…TO THE EDITOR: We read with great interest the study by Kurin et al 1 about the clinical characteristics of patients with ineffective esophageal motility (IEM) comparing diagnosis according to the Chicago classification version 3.0 (CC v3.0) versus CC v4.0.…”
mentioning
confidence: 99%
“…Kurin et al 1 demonstrated that 41 patients out of the 66 patients selected with IEM at high-resolution manometry (HRM) according to CC v3.0 also met the criteria for IEM according to the new CC v4.0. This subgroup of 41 patients had higher acid exposure time (especially in the supine position), lower adequate peristaltic reserve and higher Demeester score.…”
mentioning
confidence: 99%